An Overview of CMIP5 and CMIP6 Simulated Cloud Ice, Radiation Fields, Surface Wind Stress, Sea Surface Temperatures, and Precipitation Over Tropical and Subtropical Oceans. Issue 15 (7th August 2020) - Li, J.‐L. F.; Xu, K.‐M.; Jiang, J. H.; Lee, Wei‐Liang; Wang, Li‐Chiao; Yu, Jia‐Yuh; Stephens, G.; Fetzer, Eric; Wang, Yi‐Hui
Abstract: The potential links between ice water path (IWP), radiation, circulation, sea surface temperature (SST), and precipitation over the Pacific and Atlantic Oceans resulting from the falling ice radiative effects (FIREs) are examined from Coupled Model Intercomparison Project phase 5 (CMIP5) and phase 6 (CMIP6) historical simulations. The latter is divided into two subsets with (SON6) and without FIREs (NOS6) in CMIP6. Improvement in nonfalling cloud ice (~20 g m −2 ) is noticeable over convective regions in CMIP6 relative to CMIP5. The inclusion of FIREs in SON6 subset may contribute to reduce biases of overestimated outgoing longwave radiation and downward surface shortwave and underestimated reflected shortwave at the top of the atmosphere (TOA) by magnitudes of ~8 W m −2 over convective regions against CERES, compared to NOS6 subset. The reduced biases in radiative fluxes in convective regions stabilize the atmosphere and lead to circulation, SST, cloud, and precipitation changes over the trade wind regions, as seen from improved radiative fluxes (~15 W m −2 ), surface wind stress biases, SST (~0.8 K), and precipitation (1 mm day −1 ) biases. The significant improvement from NOS6 to SON6 leads to improved multimodel means for CMIP6 relative to CMIP5 for radiation fields over the trade wind regions but the degradation over convective zones is attributed to NOS6 subset. The results suggest that other sources of uncertainty and deficiencies in climate models may play significant roles for reducing discrepancies although FIREs, via radiation‐circulation coupling, may be one of the factors that help to reduce regional biases. Key Points: The falling ice radiative effects (FIREs) are examined for the tropical and subtropical oceans in the context of CMIP5 to CMIP6 progress As a group, CMIP6 models with FIREs have reduced biases in radiation, circulation, precipitation, and SSTs than those without FIREs Multimodel means of CMIP6 radiation fields are improved over those of CMIP5 models over trade wind region but less so in convective region